MANAJEMEN RISIKO INOVASI PRODUK OLAHAN SUSU SAPI BERDASARKAN TAHAPAN PROSES MANAJEMEN INOVASI - Winnie Septiani; M. Syamsul Maarif; Yandra Arkeman (JURNAL TEKNIK INDUSTRI, 2013)
Dairy product innovation has potential to be developed to overcome the problems of lowquality of dairy produced by the farmers. This leads to rejection of dairy by the dairy containerKoperasi Unit Desa (KUD) before getting to the Industri Pengolahan Susu (IPS) and eventuallywasted. Innovation processed products are studied in this paper is a product processed at the levelof UKM using simple processing technology. Product innovation is needed to survive in thecompetitive market, but on the other hand, an important aspect in the success of innovation thatshould be considered is the risk factor. The purpose of writing this paper is to perform a riskassessment innovation dairy cows by stage approach to innovation management processcomprising the step of searching, selection, implementation and learning. Innovation risks areidentified and analyzed based on risk inovation category consists of environmental innovation,technical resources, integration, management, marketing and strategy. The next stage is measuredand analyzed by two-dimensional measurement of the value of the probability and severity values.Furthermore the final stage of this study is to determine the risk management recommendations aremade based in the value of the ranking value risk exposure.